2019
DOI: 10.1186/s41181-019-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

AAZTA5/AAZTA5-TOC: synthesis and radiochemical evaluation with 68Ga, 44Sc and 177Lu

Abstract: Purpose AAZTA (1,4-bis (carboxymethyl)-6-[bis (carboxymethyl)]amino-6-methylperhydro-1,4-diazepine) based chelators were initially developed in the context of magnetic resonance imaging. First radiochemical studies showed the capability of AAZTA to form stable complexes with radiolanthanides and moderately stable complexes with 68 Ga. For a systematic comparison of the labelling capabilities with current diagnostic and therapeutic trivalent radiometals, AAZTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 25 publications
3
55
0
Order By: Relevance
“…1), which forms kinetically inert and thermodynamically stable Sc(III)-complexes at room temperature and provides a viable alternative to DOTA. 24,25 However, the hydrophilicity of the corresponding complexes can result in accelerated excretion and diminished accumulation in the site of interest. We sought to develop alternative, more lipophilic chelator structures that would enable robust room temperature radiolabeling with Sc(III) isotopes and form kinetically inert complexes, especially in their bifunctional form.…”
Section: Introductionmentioning
confidence: 99%
“…1), which forms kinetically inert and thermodynamically stable Sc(III)-complexes at room temperature and provides a viable alternative to DOTA. 24,25 However, the hydrophilicity of the corresponding complexes can result in accelerated excretion and diminished accumulation in the site of interest. We sought to develop alternative, more lipophilic chelator structures that would enable robust room temperature radiolabeling with Sc(III) isotopes and form kinetically inert complexes, especially in their bifunctional form.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to develop chelator systems allowing labelling under so-called "kit conditions" (room temperature, pH 5-6). Recently, 6-Amino-6-(5-methoxy-5-oxopentyl)-1,4-diacepine-tetraacetate (AAZTA-5) was introduced and demonstrated that by conjugation to TOC labelling with lutetium-177 in high yield was possible with low tracer amounts in less than 10 min at room temperature at a pH between 4.5 and 5.5 [104].…”
Section: Yttrium Lutetiummentioning
confidence: 99%
“…Radiolabeling of DOTA-SA with 177 Lu Radiolabeling of AAZTA 5 -SA-bevacizumab and DOTA-SAbevacizumab with 177 Lu and puri cation of [ 177 (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) MBq in 14-50 µL 0.04 M HCl) was diluted with 0.5 M HEPES-buffer (pH 7) to a total volume of 550 µL. Afterwards a solution of either AAZTA 5 -SA-bevacizumab (125-900 µg, 0.8-6.0 nmol) or DOTA-SA-bevacizumab (272-900 µg, 1.8-6.0 nmol) in PBS (450 µL) was added and the mixture (1 mL) was shaken for 60-90 min at 550 rpm and either at room temperature or 37 °C via thermomixer.…”
Section: Organic Synthesismentioning
confidence: 99%
“…The tert-butyl-protected derivative of AAZTA 5 (4, Fig. class="InternalRef">2) could be successfully synthesized with an overall yield of 32% within four steps according to the work recently published by our group (Sinnes et al 2019). The initial step rst includes an in situ ring-opening reaction of 2nitrocyclohexane followed by formation of the diazepane scaffold via double Nitro-Mannich reaction of the resulting nucleophilic compound with N,N'-dibenzylethylenediamine and paraformaldehyde.…”
Section: Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation